2016
DOI: 10.1111/gcb.13384
|View full text |Cite
|
Sign up to set email alerts
|

Plant invasion is associated with higher plant–soil nutrient concentrations in nutrient‐poor environments

Abstract: Plant invasion is an emerging driver of global change worldwide. We aimed to disentangle its impacts on plant-soil nutrient concentrations. We conducted a meta-analysis of 215 peerreviewed articles and 1233 observations. Invasive plant species had globally higher N and P concentrations in photosynthetic tissues but not in foliar litter, in comparison to their native Accepted ArticleThis article is protected by copyright. All rights reserved.competitors. Invasive plants were also associated with higher soil C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
149
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(173 citation statements)
references
References 65 publications
15
149
2
2
Order By: Relevance
“…, Sardans et al. ), that available N and P increase in soils that have been invaded by invasive plants. This allows us to discard the possibility that soil microbes might respond to invasion by downregulating enzyme production in response to increases in soil nutrient availability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Sardans et al. ), that available N and P increase in soils that have been invaded by invasive plants. This allows us to discard the possibility that soil microbes might respond to invasion by downregulating enzyme production in response to increases in soil nutrient availability.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, for example, Sardans et al. () reported that the concentrations of soluble nitrate and Olsen‐P are 117% and 21% higher in soils under invasive plants than under corresponding native plant communities (Fig. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the important aspects of invasibility, higher N and P availabilities potentially improve the invasion potential and productivity of invasive plants (Milbau et al., ), and invasion itself can alter soil N and P cycles (Ehrenfeld, ; Lee et al., ; Sardans et al., ). A positive feedback between exotic plant invasion and soil nutrient availabilities has been demonstrated by higher N and P concentrations and net production rates of N and available P in soils under invasion (Ehrenfeld, ; Lee, Flory, & Phillips, ), and attributed to (a) increased litter input and decomposition rates associated with invasion (Jo, Fridley, & Frank, ; Lee et al., ) and (b) modified microbial function and composition associated with soil N transformations (such as ammonia‐oxidizing bacteria; Hawkes, Wren, Herman, & Firestone, ; McLeod et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…To address this gap in knowledge, we investigated the species richness, above‐ground biomass and leaf and soil N and P concentrations and δ 15 N values in tropical ecosystems without invasion and with different invasive pressures of exotic Compositae plants ( C. odorata and A. adenophora ) in Xishuangbanna, SW China. The study is predicated on two testable hypotheses: (a) invasive plants have higher leaf N and P levels than natives through both their enhanced competitional abilities and the increasing of soil N and P availability under invasion (Ehrenfeld, ; Lee et al., ; Sardans et al., ); and (b) invasion affects native species beneficially in terms of N use while P use is compromised in the relatively N‐rich but P‐poor environment. Verification of these nutrient utilization responses has important implications for the understanding of invasion and coexistence.…”
Section: Introductionmentioning
confidence: 99%